PENGARUH KUALITAS LAYANAN BUS LISTRIK TERHADAP KEPUASAN KAUM MUDA YANG MEMPENGARUHI KEPUASAN HIDUP - Ahmad Saifulloh; Yenita (GoAcademica Research dan Publishing, 2023)
This study aims to analyze the influence of electric bus service quality on youth satisfaction which affects life satisfaction. This research uses descriptive quantitative research. The method of analysis uses software applications in SPSS version 25 which is used to analyze respondent data. Data collection was carried out using a questionnaire. The sample in this study is a portion of the population that meets the inclusion criteria, namely those who use the bus at least 2 times a month and the exclusion criteria for officers working in Trans Jakarta. The results of this study are: 1) The proportion of respondents' tangible bus variables in terms of customer satisfaction is mostly good (76.5%); 2) The proportion of respondents' bus driver's quality variables in terms of customer satisfaction is mostly good (94.1%); 3) The proportion of respondents' empathy variables in terms of customer satisfaction is mostly good (65.9%); 4) The proportion of the variable total service quality of respondents in terms of customer satisfaction is mostly good (51.8%); 5) There is a relationship between tangible bus variables and customer satisfaction (p value 0.000); 6) There is no relationship between bus driver's quality variables and customer satisfaction (p value 1000); 7) There is no relationship between empathy and customer satisfaction (p value 0.174); and 8) There is a relationship between total service quality variables and customer satisfaction (p value 0.010).